Sucrose Osmotic Treatment Effect on Moisture, Antioxidant, Texture, and Sensory Properties of Ginger Extract-Imersed Coconut Chips - Kawiji, Kawiji; Siahaan, Adrian Hotma James; Manuhara, Godras Jati; Atmaka, Windi (Journal of Applied Agricultural Science and Technology, 2024)
In this study, ginger extract was used to impart a distinctive, popular flavor and functional properties (antioxidants) to coconut chips. Sucrose was added to the extract as an osmotic agent to facilitate the migration of antioxidant and flavor compounds from the ginger extract into the fresh coconut flesh during immersion. This study aimed to determine the effects of immersion in ginger extract with the addition of various concentrations of sucrose on the antioxidant, moisture, texture, and sensory characteristics of green coconut chips. The antioxidant activity was analyzed by 2,2-diphenyl-1-picrylhydrazyl scavenging assay. Instrumental texture analysis included Fmax, hardness, and deformation parameters. The results showed that higher concentrations of sucrose added to the ginger extract resulted in increasing antioxidant activity, Fmax, hardness, and panelist preference for color, taste, and overall, and decreasing moisture and deformation. Based on the antioxidant activity parameter, adding sucrose to ginger extract enhanced the effectiveness of immersion, thereby reducing the immersion duration to achieve greater antioxidant activity.